Estilo de aprendizaje y la comprensión lectora de los estudiantes de 5to EGB de la Escuela Jesús Martínez Parroquia Clemente Baquerizo, cantón Babahoyo, Provincia de Los Ríos - Sobeny Robys, Melissa Paola (2020)
LEARNING STYLE AND READING UNDERSTANDING: In the present work, practical phase of research; The problem will be approached from a real perspective with the fifth-year students of basic general education of the “Jesús Martínez” school of the Babahoyo canton. The study is of simple descriptive design with qualitative - quantitative approximation. By motivating us to carry out this study, it is knowing that in the aforementioned institution, this process is used very little, so in this work, we will motivate students through teachers to use varied models and styles for learning significant; where all members know how to develop cognitive skills with academic performance skills, therefore, it is to know that reading must be understood from the open singular prism; looking like the prism glimpses, radiant and beautiful colors, so it must be learning, where the student feels happy and eager to learn since its variation, around the teaching it receives is diverse, motivates creativity to learn and Perform optimal and disciplined tasks. Learning styles will have a significant influence on the process of apprehension of students, which will be corroborated in the relevant part based on theoretical support. The purpose of this project is to institute competitive students.